General Perspective Of Age And Acquisition In Students' Second Language Acquisition (Sla) To Enhance In Learning L2 - Triana Wuri Cahyanti (Dharma Pendidikan, 2018)
Recently, the teacher can see that the manageable stockpile of researh of just a few decades ago has been replaced by a coordinated, systematic store house of information. Researchers around the world are meeting, talking exchanging findings, comparing data and arriving at some mutually acceptable explanations. In language arts education, or example, teacher trainees are required to study first language acquisition, particularly acquisition after age five. in order to improve their understanding of the task of teaching language skills to native speakers. In foreign language education, most standard texts and curricula now include some introductory material in first language acquisition. The reasons for this are clear. The learners age five. in order to improve their understanding of the task of teaching language skills to native speakers. In foreign language education, most standard texts and curricula now include some introductory material in first language acquisition. The reasons for this are clear. First language acquisition starts in very early childhood, but second language acquisition can happen in childhood, early or late, as well as in adulthood. Do childhood and adulthood. and differences between them, hold some keys to language acquisition models and theories? The purpose of this article is to address some of those questions and to set forth explicitly some of the parameters for looking at the effects of age and aacquisition and also in their motivation.